Leveraging genetic data to investigate the effects of interleukin‐6 receptor signalling on levels of 40 circulating cytokines. Issue 3 (7th October 2021) - Rahman, Rezbieara P.; McEwan, Lauren; Ryan, David K.; Gill, Dipender
Abstract : Interleukin 6 (IL‐6) is a circulating cytokine implicated in inflammatory processes. However, the broad effects of IL‐6 receptor (IL‐6R) signalling on other circulating cytokines is not known. Using summary‐level data from genome‐wide association studies, we leveraged genetic variants that proxy IL‐6R signalling in two‐sample Mendelian randomization analyses to investigate effects on levels of 40 circulating cytokines. Increased genetically proxied IL‐6R signalling was associated with reduced levels of 10 circulating interleukins, chemokines and growth factors. The significant results include IL‐10 (Mendelian randomization estimate −0.306, standard error [SE] 0.093), IL‐4 (estimate −0.393, SE 0.1007), eotaxin (estimate −0.510, SE 0.1213) and Fibroblast growth factor (estimate −0.334, SE 0.1005). The findings from this study support the feedback effects of IL‐6R signalling on reducing levels of some circulating cytokines and identify compensatory mechanisms that maybe modulating its inflammatory effects. These results provide insight into the mechanisms by which IL‐6R signalling may be contributing to inflammatory and autoimmune diseases.